Interventions addressing impacts of climate change on sexual and reproductive health and rights in sub-Saharan Africa: A scoping review - Jacinter A. Amadi; George Odwe; Francis Obare; Betsy Sambai; Beth Kangwana (PLoS ONE, 2025)
Sub-Saharan Africa is faced with triple challenges of high vulnerability to climate change impacts, high levels of inequality, and poor sexual and reproductive health and rights (SRHR) outcomes. Climate change impacts can worsen the SRHR situation for high-risk groups such as women, children, adolescent girls, and people living with Human Immunodeficiency Virus (HIV). This scoping review examined interventions addressing the impacts of climate change on SRHR in the region to identify barriers to and facilitators of effective integration. The review followed Arksey and O’Malley’s framework for scoping reviews. Data search was conducted in peer-reviewed journal databases and from grey literature on the official websites of selected organizations. Data charting was conducted using the Population, Intervention, Comparator, Outcome tool in Covidence. There is limited evidence on interventions at the intersection of climate change and SRHR, with seven (7) documents included in the review. Maternal and Child Health, HIV prevention, and a combination of maternal and child health and family planning were the SRHR components addressed. Other components like Gender-based violence, harmful practices, and abortion care do not have targeted interventions. A siloed approach to SRHR and climate change programming impedes intervention integration. Documented interventions are implicit about climate risks, focus on impact pathways, and do not directly target SRHR. There are no interventions targeting vulnerable and marginalized groups. Limited policy integration, financial constraints, and poor SRHR recognition deter intervention integration. Effective and equitable integration requires that population growth impacts and SRHR issues be recognized and deliberate investments (research, policies, programs, interventions, and financing) put in place to address critical SRHR gaps and climate vulnerabilities to enhance resilience.